Degradasi Tradisi Betangas Pada Masyarakat di Kecamatan Selangit Kabupaten Musi Rawas - Safariza Setyowati Safariza; Ira Miyarni Sustianingsih; Agus Susilo (LP4MK STKIP PGRI Lubuklinggau, 2023)
This study aims to describe the degradation of betagas in the community in Selangit District, Musi Rawas Regency. The method used in this research is qualitative. The steps used include: Observation, Interview, and Documentation. The results of the study contain a description of the form of degradation of the betangas tradition which includes the lack of preservation of local culture from the local community and the change in alternative treatment from traditional to modern due to the progress of the times that are increasingly developing. Then the factors that influence the degradation of the betangas tradition in the community in Selangit District are the increase in knowledge, technological advances, and the lack of communication between generations about the betangas tradition. That is what has resulted in the degradation of the betangas tradition in Selangit District.